Manual of lung transplant medical care - Hertz, Marshall, I (Fairview Publications, 2001)
Describes the optimal procedures to follow in the care of the lung transplant patient - beginning prior to the time of first referral and continuing through the rest of the patient\'s post-operative life.
Transplant care series
Keywords: předoperační péče; Postoperative Care; pooperační péče; anesteziologie a intenzivní lékařství; pneumologie a ftizeologie; Lung Transplantation; transplantologie; Preoperative Care; transplantace plic